The Holy Land of Saints: The Latin Patriarchate of Jerusalem and the Life Story of St. Marie Alphonsine - Maayan Karen Raveh (Religions, 2024)
Utilizing the lens of new historicism, this study examines how hagiographers Stolz, Duvignau, and Khoury, from the Latin Patriarchate of Jerusalem, have constructed and modified the narrative identity of St. Marie Alphonsine through different periods—1936, 1989, and 2012–2015. This approach illuminates the complex relationship between religious storytelling, cultural identity formation, and perceptions of “otherness”. The chronological dissection of St. Marie Alphonsine’s portrayal uncovers the hagiographers’ efforts to recalibrate her image in response to the changing cultural, spiritual, and communal demands within the Patriarchate’s jurisdiction and among the faithful. Highlighting the hagiographers’ instrumental role on behalf of the Patriarchate in molding religious and cultural discourses, the article explores the profound impact of saintly veneration on shaping the religious identity and cultural narratives of the Catholic community in the Holy Land. It underscores the essential function of the Patriarchate in steering the Catholic community through the complexities of the evolving socio-religious landscape.